Polymorphous Low-Grade Neuroepithelial Tumor of the Young (PLNTY): A Newly Described Entity of Special Radiological Significance - Barretto, Brendon B.; Mani, Jayanti; Venkatraman, S.; Kumar, Abhaya; Rao, Shilpa; Kale, Hrishikesh (Indian Journal of Radiology and Imaging, 2023)
Intracranial granulomas are a major cause of seizures in India, the most common etiologies being neurocysticercosis and tuberculosis. However, other pathologies including rare low-grade tumors may mimic these granulomas on imaging. In this article, we presented the case of a young woman patient with drug-resistant epilepsy. On imaging, there was a small calcified lesion in the brain parenchyma. In view of concordant electroclinical and imaging data on presurgical evaluation, the lesion was excised and the patient was seizure free. On histopathological evaluation, it was found to be a polymorphous low-grade neuroepithelial tumor of the young (PLNTY) – a rare, recently reported entity that can mimic an intracranial granuloma on imaging.
Keywords: intracranial granuloma; polymorphous low-grade neuroepithelial tumor of the young; seizures